PENDIDIKAN MULTIKULTURAL PERSPEKTIF AL-QUR’AN DAN HADITS - Muhammad Umar Hasibullah (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2023)
God's will for mankind to be different is not without reason, with differences, it is hoped that there will be an attitude of mutual understanding, help, to realize man's main task on the surface of the earth as a caliph who builds and prospers the life of the world. Although, in the history of mankind, there have been many heartbreaking sad stories resulting from the existence of interracial and ethnic conflicts. The occurrence of community society is a necessity, occurring as a sunnatulla>h which is undeniable. Everyone will not be able to make ends meet on their own without the help of others. Man never finds himself alone on this earth. It always finds other humans living nearby on the same planet. Therefore, every person must desire all that is useful to him, just as he also knows that others have the same desires as his desires and have the same expectations The research method used is descriptive qualitative. The results showed that the multicultural education in the perspective of the Qur'an and Hadith is 1) Seeking and strengthening similarities in differences (Kalimatun Sawa) The differences do not need to be sought, because without being sought, the differences will remain. It is easy to find differences, because those differences are sunnatullah to distinguish one from another. Allah Almighty. creating all his creatures is different including humans who are created differently. 2) Mutual Trust and Mutual Understanding (Wasathiyah) Mutual trust will arouse enthusiasm and increase motivation in carrying out an activity. Everyone does not rule out the possibility of making a mistake, if it happens, this is where mutual trust will be seen. 3)Tolerance (Tasamuh) Tolerance comes from the word tolerant which means the nature or attitude of tolerance, respect, allowing, allowing stances, opinions, views, beliefs, habits, and behaviors that are different or contrary to one's own stance and do not vilify each other in differences. (Language Center of the Ministry of Education and Culture, 2011).